(untitled) (Academicia Globe: Inderscience Research, 2023)
This article discusses the problem of using modern technologies in teaching a foreign language to increase motivation for the subject and the quality of education. The principles and methods of the system-activity approach in teaching foreign languages are considered, as well as a number of modern pedagogical technologies used in teaching English.